2013
DOI: 10.1016/j.jfoodeng.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical properties of sodium and calcium caseinate edible active films with carvacrol

Abstract: Please cite this article as: Arrieta, M.P., Peltzer, M.A., Garrigós, a.d.C., Jiménez, A., Structure and mechanical properties of sodium and calcium caseinate edible active films with carvacrol, Journal of Food Engineering (2012), doi: http://dx.doi.org/10. 1016/j.jfoodeng.2012.09.002 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 45 publications
10
93
0
9
Order By: Relevance
“…The studied active agents are more effective against Gram‐negative bacteria, E. coli , than against Gram‐positive bacteria, L. innocua . On the contrary, other studies performed with antimicrobial films containing the same active compounds showed higher antimicrobial activity against Gram‐positive cells, without an outer membrane . However, Aldana et al have also observed a higher antimicrobial activity of films with lime EO against Gram‐negative bacteria.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The studied active agents are more effective against Gram‐negative bacteria, E. coli , than against Gram‐positive bacteria, L. innocua . On the contrary, other studies performed with antimicrobial films containing the same active compounds showed higher antimicrobial activity against Gram‐positive cells, without an outer membrane . However, Aldana et al have also observed a higher antimicrobial activity of films with lime EO against Gram‐negative bacteria.…”
Section: Resultsmentioning
confidence: 87%
“…The incorporation of pure CA or EU enhances the thermal sensitivity of PHBV, decreasing the onset and peak of degradation temperature, whereas the whole essential oils (OR and CLO) slightly promote the thermal stability of the polymer. Incorporation of some additives to polymer matrices usually results in a reduction of the thermal resistance of the network due to the weakening effect of the chain bonds . Nevertheless, some authors reported an increase in the polymer thermal resistance when some essential oils are added.…”
Section: Resultsmentioning
confidence: 99%
“…Films were prepared by the solvent casting method as reported by Arrieta, Peltzer, Garrigós, and Jiménez (2013). Sodium caseinate and glycerol was purchased from Sigma-Aldrich (Dublin, Ireland …”
Section: Methodsmentioning
confidence: 99%
“…Arrieta et al . () reported that caseinate films containing 15.0% glycerol exhibited higher TS and lower E compared to the films containing 25.0% and 35.0% glycerol. Jia et al .…”
Section: Resultsmentioning
confidence: 97%